2011
DOI: 10.1109/tpwrd.2010.2081384
|View full text |Cite
|
Sign up to set email alerts
|

Grid Interconnection of Renewable Energy Sources at the Distribution Level With Power-Quality Improvement Features

Abstract: Renewable energy resources (RES) are being increasingly connected in distribution systems utilizing power electronic converters. This paper presents a novel control strategy for achieving maximum benefits from these grid-interfacing inverters when installed in 3-phase 4-wire distribution systems. The inverter is controlled to perform as a multi-function device by incorporating active power filter functionality. The inverter can thus be utilized as: 1) power converter to inject power generated from RES to the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
151
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(154 citation statements)
references
References 13 publications
(11 reference statements)
0
151
0
3
Order By: Relevance
“…According to the matrix converter the expectations of the output voltage, it can calculate the corresponding rotating the voltage space vector, which is based on the current to the output of a maximum of line voltage to fit the expect voltage space vector. The theory and simulation analysis show that this control can effectively reduce the distortion of output voltage and input current waveform [5].…”
Section: Introductionmentioning
confidence: 93%
“…According to the matrix converter the expectations of the output voltage, it can calculate the corresponding rotating the voltage space vector, which is based on the current to the output of a maximum of line voltage to fit the expect voltage space vector. The theory and simulation analysis show that this control can effectively reduce the distortion of output voltage and input current waveform [5].…”
Section: Introductionmentioning
confidence: 93%
“…RES are represented as current sources connected to the dc-link of a grid-interfacing inverter. The current injected by renewable into dc-link at voltage level Vdc can be given as (1) Where P RES is the power generated from RES. The current flow on the other side of dc-link can be represented as, (2) Where, P INV -total power available at grid-interfacing inverter side, P G -active power supplied to the grid and inverter losses, and P LOSS -inverter losses.…”
Section: Voltage and Power Control Operationmentioning
confidence: 99%
“…To achieve more benefits from grid-interfacing inverters using 3-phase 4-wire distribution systems are explained by the Singh et al [14]. Here authors have demonstrated and simulated using Matlab / Simulink and it is validated through DSP processor based results.…”
Section: Related Workmentioning
confidence: 99%